Issues in the Diagnosis and Management of Hereditary Antithrombin Deficiency. (September 2016) - Bauer, Kenneth A.; Nguyen-Cao, Tam M.; Spears, Jeffrey B.
Objective: To review insights gained in the past several years about hereditary antithrombin (AT) deficiency and to outline approaches to the management of patients with AT deficiency in the acute and chronic settings.Data Sources: An extensive literature search of Scopus (January 2008-April 2016) was performed for the terms congenital antithrombin deficiency, inherited antithrombin deficiency, or hereditary antithrombin deficiency . Additional references were identified by reviewing literature citations.Study Selection: All relevant English-language case reports, reviews, clinical studies, meeting abstracts, and book chapters assessing hereditary AT deficiency were included.Data Synthesis: AT deficiency significantly increases the risk of venous thromboembolism (VTE). The risk of VTE is particularly high during pregnancy, the postpartum period, and following major surgery. Effective clinical management includes determination of the appropriate type and duration of antithrombotic therapy (ie, AT replacement for acute situations) while minimizing the risk of bleeding. For persons newly diagnosed with AT deficiency, age, lifestyle, concurrent medical conditions, family history, and personal treatment preferences can be used to individualize patient management. Patients should be informed of the risks associated with hormonal therapy, pregnancy, surgical procedures, and immobility, which further increase the risk of VTE in patients with AT deficiency.Conclusion: AT deficiency poses the highest risk for VTE among the hereditary thrombophilias, often requiring long-term anticoagulation. Undertaking an evaluation for hereditary thrombophilia is controversial; however, a diagnosis of VTE in association with AT deficiency can have management implications. An important treatment option for patients with this disorder in high-risk situations is AT concentrate.